Studies in applied welfare analysis papers from the third ECINEQ meeting - Bishop, John A. (Emerald, 2010)
This volume contains papers from the Society for the Study of Economic Inequality's third meeting held in Buenos Aries, Argentina, in July 2009. The first five papers focus on a number of Latin American countries, on the understudied topics of poverty and inequality in these areas. Specific issues covered by these papers include multidimensional poverty, equity effects of school drop-outs, and the role of transfer programs in reducing Latin American poverty. Additional papers provide research from further afield including China and France and cover topics such as: relative deprivation; taxation and inequality; mobility dominance; polarization; estimation of child costs; nutritional inequality; and transportation inequalities. The volume includes work by such well-known authors as Jacques Silber, Jean-Yves Duclos, and Udo Ebert. This book is the 18th Volume in the notable Research on Economic Equality series which offers fresh theoretical and methodological insights into the key issues in the field of economic inequality, showcasing highly topical work from both senior researchers and emerging scholars.
Keywords: Poverty -- Congresses.; Income distribution -- Congresses.; Poverty -- Latin America -- Congresses.; Income distribution -- Latin America -- Congresses.; elektronické knihy; electronic books